Mapping the conformational dynamics and pathways of spontaneous steric zipper Peptide oligomerization. - Dirk Matthes (Public Library of Science (PLoS), 2011)
The process of protein misfolding and self-assembly into various, polymorphic aggregates is associated with a number of important neurodegenerative diseases. Only recently, crystal structures of several short peptides have provided detailed structural insights into -sheet rich aggregates, known as amyloid fibrils. Knowledge about early events of the formation and interconversion of small oligomeric states, an inevitable step in the cascade of peptide self-assembly, however, remains still limited. We employ molecular dynamics simulations in explicit solvent to study the spontaneous aggregation process of steric zipper peptide segments from the tau protein and insulin in atomistic detail. Starting from separated chains with random conformations, we find a rapid formation of structurally heterogeneous, -sheet rich oligomers, emerging from multiple bimolecular association steps and diverse assembly pathways. Furthermore, our study provides evidence that aggregate intermediates as small as dimers can be kinetically trapped and thus affect the structural evolution of larger oligomers. Alternative aggregate structures are found for both peptide sequences in the different independent simulations, some of which feature characteristics of the known steric zipper conformation (e.g., -sheet bilayers with a dry interface). The final aggregates interconvert with topologically distinct oligomeric states exclusively via internal rearrangements. The peptide oligomerization was analyzed through the perspective of a minimal oligomer, i.e., the dimer. Thereby all observed multimeric aggregates can be consistently mapped onto a space of reduced dimensionality. This novel method of conformational mapping reveals heterogeneous association and reorganization dynamics that are governed by the characteristics of peptide sequence and oligomer size.